2020
DOI: 10.1002/app.50220
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/gelatin‐based bioactive and antibacterial coatings deposited via electrophoretic deposition

Abstract: The fabrication of biocompatible and antibacterial coatings on metallic implants remains a significant challenge for load‐bearing orthopedic implants. This study focuses on the electrophoretic deposition of chitosan/gelatin/Ag‐Mn doped mesoporous bioactive glass nanoparticles (Ag‐Mn MBGNs) composite on the PEEK/bioactive glass layer (called as multi‐structured coatings), which had been deposited electrophoretically on 316L stainless steel. The EPD parameters for the deposition of the chitosan/gelatin/Ag‐Mn MBG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The in-vitro bioactivity of the Ag-EPD and EPD/ RF-20 samples was not investigated in this work. In fact, the in vitro bioactivity of PEEK/BG coatings is well established and has been reported in our previous studies [24,28,45]. Here, we conducted in vitro bioactivity studies only on EPD/RF-40 samples in order to confirm that the top layer does not affect the bioactive character of the underlying PEEK/BG/ MBGNs layer.…”
Section: In Vitro Bioactivity Assessmentmentioning
confidence: 65%
“…The in-vitro bioactivity of the Ag-EPD and EPD/ RF-20 samples was not investigated in this work. In fact, the in vitro bioactivity of PEEK/BG coatings is well established and has been reported in our previous studies [24,28,45]. Here, we conducted in vitro bioactivity studies only on EPD/RF-40 samples in order to confirm that the top layer does not affect the bioactive character of the underlying PEEK/BG/ MBGNs layer.…”
Section: In Vitro Bioactivity Assessmentmentioning
confidence: 65%
“…However, the cytotoxic effect associated with the release of Ag ions can be co-doped by the addition of Sr ions. In our previous study, we have shown that the toxic effect of Ag can be minimized by the co-substitution of Sr and Mn along with the Ag [1,6,21]. Therefore, this study presents a new frontier in the field of biomedical materials by the use of co-substituted Ag and Sr ions.…”
Section: Disc Diffusion Test (Inhibition Halo Method)mentioning
confidence: 86%
“…MBGNs assimilated with Ag are supportive for ion release and enhanced bacterial inhibition. Ag-doped BG is a promising dental material as dental implants are frequently exposed to bacteria [19][20][21]. MBGNs combined with Ag nanoparticles indicate a bactericidal effect against Enterococcus faecalis, which exists in the root canal system without inducing cytotoxicity on mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the cytotoxic effect associated with the release of Ag ions can be copedby the addition of Sr ions. In our previous study, we have shown that the toxic effect of Ag can be minimized by the co-substitution of Sr and Mn along with the Ag [1, 6,22]. Therefore, this study presents new frontier in the field of biomedical materials by the use of co-substituted Ag and Sr ions.…”
Section: Disc Diffusion Test (Inhibition Halo Method)mentioning
confidence: 94%
“…On the other hand, mesoporous silica have pores in the range of 2 -50 nm which increase the surface area, and serve as a channel for adsorption/desorption of drugs for targeted drug delivery system [20][21][22]. Moreover, the therapeutic release of antibacterial and bioactive ions is anticipated to inhibit biofilm formation and resultant agony from infection, which is the main objective of this research work [21,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%